Adaptive Discrete Models of Functionally Represented Object Shapes - Choporov, S.V. (Проблеми машинобудування, 2018)
In this paper, a method is proposed for constructing adaptive discrete models of object shapes represented functionally. This method uses an estimate of the accuracy of the finite element analysis to determine the areas where nodes and elements are refined. In the process of refinement, the refinement templates of elements are used that are proposed for the most common elements (triangles, quadrangles, tetrahedra and hexagons), with reprojection on the domain boundary of boundary nodes. Examples of constructing adaptive discrete models for solving two- and three-dimensional problems of studying stress-strain state are shown.